Well-differentiated HPV-independent gastric-type adenocarcinoma of the cervix: a case report and literature review - Wang, Weijun; Cai, Yuan; Ren, Zhuanqin; Tian, Hongzhe; Liu, Xia (Frontiers in Oncology, 2025)
BackgroundWell-differentiated HPV-independent gastric-type endocervical adenocarcinoma (formerly termed minimal deviation adenocarcinoma) is a rare, aggressive cervical cancer that is challenging to diagnose because its histologic features can be very similar to benign endocervical glands or even normal glands. The imaging features and clinical manifestations are also non-specific, with the disease often having an insidious onset. However, this tumor exhibits a high degree of aggressiveness and tends to progress rapidly; as a result, it is frequently diagnosed at an advanced stage, missing the optimal window for treatment. Therefore, thorough investigations are required to identify specific pathological features unique to this condition to improve imaging and the early diagnosis rate.Case introductionThis article reports a case of a 42-year-old female patient who was hospitalized for 2 months due to vaginal discharge and 1 week of lower abdominal pain. Upon physical examination, a small amount of odorless, transparent secretion was detected in the vagina; the cervix appeared enlarged, and a mass measuring approximately 6 cm was palpable in the right adnexal region. The pelvic MRI indicated the presence of malignant cervical lesions, potentially cervical gastric-type adenocarcinoma, accompanied by significant pericervical invasion. Colposcopy also suggested the presence of cervical adenocarcinoma. Following the exclusion of any surgical contraindications, robotic-assisted laparoscopic extensive hysterectomy and bilateral adnexectomy were performed under general anesthesia. Postoperative pathological examination confirmed the presence of invasive cervical adenocarcinoma, independent of HPV. The subtype identified was classified as gastric-type adenocarcinoma, exhibiting locally well-differentiated characteristics.ConclusionHighly differentiated HPV-independent cervical gastric-type adenocarcinoma is insidious in onset and progresses rapidly. Clinically, it often presents with abnormal vaginal discharge or bleeding, and deep biopsy or cervical conization is often required for diagnosis. Pathologically, it is characterized by randomly distributed, highly differentiated tumoral glands, which often invade deep into the uterine wall, extending beyond 2/3 of the cervical wall. It also shows positive expression of gastric-type markers such as MUC6, Mucin 5AC, and HIK1083. Imaging examination revealed the size of the lesion, depth of infiltration, the invasion of adjacent organs, and lymph node metastasis, which is beneficial for differential diagnosis, clinical staging, and the development of a treatment plan.